2015
DOI: 10.22401/jnus.18.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic and Thermodynamic Studies of Metal Complexes with Schiff Bases Derived from 2-[5-(Pyridin-2-Ylmethylene)-amino] 1,3,4-Oxadiazol-2-yl-Phenol

Abstract: New metal complexes of the ligand 2-[5-(Pyridin-2-ylmethylene)-amino] 1,3,4-thiadiazol-2-ylphenol (L) with the metal ions Co(II), Ni(II), Cu(II) and Zn(II) were prepared in alcoholic medium. The Schiff base was condensed [2-pyridine carbxaldehyde] with [2-amino-5-(phenyl-1,3,4oxadiazole] in alcoholic medium. Two tetradentate Schiff bases ligand were used for complexation upon two metal ions of Co 2+, Ni 2+, Cu 2+ and Zn 2+ as dineucler formula M2L2. The synthesized compound and their metal complexes were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The spectra of the chromium complex observed two (428 nm, 608 nm) in Table 3, attributed to the allowed transfer 4 A 2 g → 4 T 1 g (F) and 4 A 2 g → 4 T 1 g (F) respectively [19]. It has been observed that the electron spectrum is complex cobalt(II) low spin octahedral (t 2 g 6 eg 1 ), one permissible transition 500 nm, which is 2 Eg 2 T 2 g (20).…”
Section: Electronic Spectra Magnetic Moments and Molar Conductance Of...mentioning
confidence: 99%
“…The spectra of the chromium complex observed two (428 nm, 608 nm) in Table 3, attributed to the allowed transfer 4 A 2 g → 4 T 1 g (F) and 4 A 2 g → 4 T 1 g (F) respectively [19]. It has been observed that the electron spectrum is complex cobalt(II) low spin octahedral (t 2 g 6 eg 1 ), one permissible transition 500 nm, which is 2 Eg 2 T 2 g (20).…”
Section: Electronic Spectra Magnetic Moments and Molar Conductance Of...mentioning
confidence: 99%
“…The linked nitrogen atom of thiadiazol ring shows shifted absorption bands of ligand range 1174 -1303 cm -1 in complexes which confirms the metal's binding to the group (= N-N =) 17 . For all complexes, a new beam appeared in the range 586-590 cm -1 due to the vibrations of the group stretch (M-O) 18 and showed a stretching of the group (M-N) of the prepared complexes in the bounded region between 458-495cm -1 , confirming the metal's association via the (N) atom 19 . All the infrared spectrum values for the complexes are shown in Tab.2.…”
Section: Mass Spectral Data and 1 H-nmr Of Ligandmentioning
confidence: 72%
“…Positive values for (∆H) indicate that the reactions are endothermic. The negative values indicate that the reactions are heat-emitting and the small values of the Arrhenius factor (Z) indicate that the reactions of the decomposition of ligand (LH 2 ) are fast, while the large and positive values in the state of transition can be classified as slow reactions [7][8][9]19 .…”
Section: Thermal Analysismentioning
confidence: 99%